Peran Kinerja Lingkungan, Biaya Lingkungan, Dan Carbon Emission dalam Kinerja Keuangan Perusahaan Pertambangan BEI 2021-2023 - Nanda Karisma Putri; Maria Yovita R. Pandin (CV. Ulil Albab Corp, 2025)
This study aims to analyze the influence of environmental performance, environmental costs, and carbon emissions on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A quantitative method was employed using secondary data obtained from company annual reports. The analysis results show that environmental performance has a significant positive impact on financial performance, while environmental costs have a significant negative impact. In contrast, carbon emissions do not significantly affect financial performance. These findings indicate that effective environmental management can enhance a company’s financial performance, but environmental costs must be managed efficiently. The lack of impact from carbon emissions may be due to limited market or policy attention to this issue during the study period. This research suggests that companies should improve environmental performance and cost efficiency, while regulators should strengthen sustainability policies, such as emission reduction incentives.